Investigation of stress level in wheel-rail contact - Özdemir, Yalcin; Voltr, Petr (Ústav termomechaniky AV ČR, v. v. i., 2016)
Initial calculation of the wheel and rail contact problem was solved with analytical theories. These include some assumptions during computations. A finite element analysis was performed to compare results of the analytical tools because of the assumptions. In addition, various finite element models have been developed by researchers to examine material response during wheel-rail contact. Damage of the rail surface and its effects on the contact forces are a common research area in numerical computations of wheel-rail contact. Maximum stress level of the model is a key factor of the permanent deformations. Neutral position of the wheelset is commonly selected in the studies. In this study, a wheel-rail contact tool is developed to investigate effects of cant angle and lateral position of wheel on maximum stress level that occurs in the rail part.
Vyšetřování úrovně napětí v kontaktu kolo-kolejnice
Keywords: wheel-rail contact; contact stress; lateral shift; cant angle; kontakt kolo-kolejnice, kontaktní napětí, příčný posun dvojkolí, úklon kolejnice